Análise de convergência dos retornos das ações de empresas do setor financeiro brasileiro - Matias, Gregório Pinto (2011)
This article is an analysis of the validity of the hypothesis that states the tendency of common growth presented in the evolution of the prices of 31 of the major financial stock institutions listed on BM&F Bovespa during the period of January 2000 to June 2007, based on the framework of semi-parametric Philips e Sul (2007). Since stocks are derived from the day-to-day of a business, this work seeks to show whether there are actions that converge to a certain level of real cumulative returns and, based on it, analyze what factors they have in common that will comprise each convergence club. The results obtained should add to the literature of share performance in banks and financial companies, by highlighting the existence of four convergence clubs, with their own dynamic transition, whose composition appear to have specific characteristics. The first club owns volatile shares of large institutions with a high payout and ROE, while the other ones can be associated with a reduction in both the financial indicators and other performance indicators such as the Sharpe ratio and Sortino ratio. Even if the first group, made only by multi-banks and the second by private companies it is not enough to designate a pattern from these characteristics, therefore, demystifying the questions related to the efficiency of public banks in comparison to private banks.